2019
DOI: 10.14814/phy2.14151
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine nucleotide regulation of hepatic endoplasmic reticulum calcium uptake

Abstract: Pyridine nucleotides serve an array of intracellular metabolic functions such as, to name a few, shuttling electrons in enzymatic reactions, safeguarding the redox state against reactive oxygen species, cytochrome P450 (CYP) enzyme detoxification pathways and, relevant to this study, the regulation of ion fluxes. In particular, the maintenance of a steep calcium gradient between the cytosol and endoplasmic reticulum ( ER ), without which apoptosis ensues, is achieved by an elaborate comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 77 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…MAMs are the sites of interaction between organelles ( Vance et al, 1997 ; Patergnani et al, 2011 ) and play a role not only in metabolite trafficking and signal transduction but in membrane fusion, mitophagy, and lipid metabolism ( Janikiewicz et al, 2018 ). MAM proteins are broadly classified as protein tethers, ion channels, or enzymes ( Wang et al, 2019 ) and are vulnerable to age-related dysregulation that occurs as a consequence of loss or disruption of critical metabolic fluxes ( Janikiewicz et al, 2018 ; Moltedo et al, 2019 ; Ziegler et al, 2021 ). It remains unclear whether MAM composition is implicated in the aging process ( Janikiewicz et al, 2018 ).…”
Section: Mitochondria-endoplasmic Reticulum Contacts (Mercs)mentioning
confidence: 99%
“…MAMs are the sites of interaction between organelles ( Vance et al, 1997 ; Patergnani et al, 2011 ) and play a role not only in metabolite trafficking and signal transduction but in membrane fusion, mitophagy, and lipid metabolism ( Janikiewicz et al, 2018 ). MAM proteins are broadly classified as protein tethers, ion channels, or enzymes ( Wang et al, 2019 ) and are vulnerable to age-related dysregulation that occurs as a consequence of loss or disruption of critical metabolic fluxes ( Janikiewicz et al, 2018 ; Moltedo et al, 2019 ; Ziegler et al, 2021 ). It remains unclear whether MAM composition is implicated in the aging process ( Janikiewicz et al, 2018 ).…”
Section: Mitochondria-endoplasmic Reticulum Contacts (Mercs)mentioning
confidence: 99%
“…
Wang et al (2019) propose that NADP inhibits SERCA pump and that this explains the inhibitory effect of NADP on Ca 2+ uptake by rat liver microsomes. The analysis of these data extracted from figures 2 and 10 is shown in Figure 1, the data on Ca 2+ uptake from Figure 2 by Wang et al are shown as red squares and data on Ca 2+ /Mg 2+ ATPase activity from figure 10 are shown as blue diamonds.
…”
mentioning
confidence: 93%
“…1). The authors argue that SERCA pump accounts for only 14% of the total ATPase activity (Wang et al 2019). However, this does not seem to explain that the effect of NADP on ATPase activity and microsomal Ca 2+ uptake occurs in a different concentration range resulting from different Hill coefficients.…”
mentioning
confidence: 99%
“…One function of the endoplasmic reticulum (ER) is to properly assemble proteins that are eventually destined for intracellular organelles, cytoplasm, or the cell surface [ 1 ]. In liver, the ER is the primary calcium reservoir [ 2 ] and, as such, governs the activity of multiple enzymes and chaperones involved in protein folding and ER function. To accomplish these tasks, high Ca 2+ levels in the ER are a requisite [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish these tasks, high Ca 2+ levels in the ER are a requisite [ 3 ]. Hence, in the ER, there is a thousand-fold calcium gradient over the cytosol [ 2 , 4 ]. The microsomal concentration of Ca 2+ is regulated by the coordination of contradictory fluxes across the membrane: Ca 2+ influx from the cytosol to the ER occurs mainly via the P2-ATPase ion transporter family, whereas efflux transpires through various tightly regulated ion channels [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%